IMPLEMENTASI PEMBELAJARAN TERPADU BERBASIS STEM TERHADAP KEMAMPUAN PEMECAHAN MASALAH DAN LITERASI SISWA KELAS IV SD GMIT MANUMUTI TARUS - Mbuik, Heryon Bernard; Ningsih Abigail Tasoin; Suan, Asri Marsilda; Desi Benu; Ketlin Manafe; Maria Ferdiana Bikolo; Maria Herniyati Bria; Mimi S.D Benu; Roni Roberto Seo Talan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the impact of integrated learning based on STEM (Science, Technology, Engineering, Mathematics) on the problem-solving skills and literacy of fourth-grade students at SD GMIT Manumuti Tarus. The research used a descriptive qualitative approach. The subjects were one classroom teacher and 20 students. Data collection techniques included observation, interviews, documentation, and tests. The results showed that the implementation of STEM-based integrated learning significantly improved students' abilities to solve contextual problems and enhanced their scientific and mathematical literacy. Students became more active, creative, collaborative, and reflective in addressing real-life problems around them. The STEM approach provided space for students to connect various concepts across disciplines and apply them in daily life. The learning process shifted from teacher-centered to student-centered, enabling learners to engage directly in knowledge construction activities through exploration, designing simple tools, group discussions, and project presentations. This research confirms that integrated learning based on STEM can foster students' critical thinking, problem-solving skills, and literacy development in primary education contexts